The Impact of Value and Spiritual Approaches in the Change of Juvenile Delinquency - Muhammad Adnan Alkatiri; Maemonah Maemonah; Neni Simbala (State Islamic Institute of Manado (IAIN) Manado, Indonesia, 2021)
This study aims to describe the efforts made by a teenager about his behavior changes that are more meaningful and religious as a result of the value and spiritual approaches. This study uses a descriptive qualitative method. Data were collected using observation and interview techniques to a single subject who experienced changes in behavior as a result of the two approaches. The results reveal that the efforts to change the subject's behavior are driven by (1) feelings of guilt and deep regret when reminiscing about their juvenile delinquency, (2) various daily positive activities that have been carried out by the subject, and (3) a circle of friends and an environment that respects high social and spiritual values.